百度试题 结果1 题目Find the general solution of the differential equation$$ y ^ { \prime \prime } + 9 y = 0 . $$ 相关知识点: 试题来源: 解析 $$ y ( t ) = A \sin ( 3 t ) + B \cos ( 3 t ) $$ 反馈 收藏
Find the general solution of x double prime + x prime + 4x = 0. Find the general solution to the following: y double prime + 3*y prime + 2y = 1/(1 + e^x). Determine the general solution to y double prime - 4*y prime - 15y = 0. Find a general solution to y triple pr...
8. Find the general solution of y′′−xf(x)y′+f(x)y=0. 9. Verify that one solution of xy′′−(2x+1)y′+(x+1)y=0 is given by y1=ex, and find the general solution. 10. (a) If n is a positive integer, find two...
Find the general solution to each differential equation. a) y''+6y'+9y=0 b) y''+2y'-8y=0 c) y''+6y'+13y=0 d) x^2y''+xy'+4y=0 e) y''+4y'+8y=0 f) y''-4y'+4y=0 g) x^2y''-4xy'+4y=0 h) y''-2y'+4y=0 i) y^(4 Find the general solution of the...
Apply chain rule to solve given problem {eq}\displaystyle y = \frac{{{e^x} - {e^{ - x}}}{2}\\ \displaystyle \frac{{dy}}{{dx}} = \frac{{d\left(...Become a member and unlock all Study Answers Start today. Try it now Create an account Ask a question Our experts can...
Answer to: Find the exact solution of the initial value problem. Indicate the interval of existence. y' = \frac {-2t(1 + y^2)}{y} , y(0) = 1 By...
You'll get a detailed solution from a subject matter expert that helps you learn core concepts.See Answer Question: Find the general solution to y′′−12y′+36y=0. Enter your answer as y=?. In your answer, use c1 and c2 to denote arbit...
The complementary function and specific integral must first be located in order to arrive at the general solution of the differential equation, which is as follows {eq}y(x)=y_c+y_p{/eq}. Answer and Explanation: {eq}\text{Consider the differential equa...
Given f(x) = (x^-5 + 1)((3x + 2)/(x)), find f prime (x). Find a particular solution to 4*y double prime + 12*y prime + 9y = t^(-2) e^(-3/2t). Factor the polynomial as much as possible or say it is prime : X^3 - 8Y^3. Factor ...
Find a differential equation of the form y'' + a_1y' + a_0y = 0 satisfied by the function y(t) = e^t - 5e^{-3t}. Solve for the coefficients a_1 and a_0. Find the general solution to the following partial differential equation. 4 u_x + 2...